1980
DOI: 10.1007/bf01757303
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of shoshin beri beri with hemodynamic and plasma catecholamine data

Abstract: Two fulminant forms of beri beri ("shoshin beri beri") have been the subject of detailed study; circulating catecholamines reached very high levels. The evolution of hemodynamic parameters after treatment with thiamin is described. One case died and the histological lesions corresponded to those of "chronic congestive beri beri".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Shoshin beriberi is the fulminant form of this disease and is characterized by hypotension, tachycardia, and lactic acidosis (1)(2)(3)(4)(5)(6). While thiamine deficiency is also associated with ST-segment elevation in some animal models (7,8), there has been no report of ST-segment elevation in humans with beriberi.…”
Section: Introductionmentioning
confidence: 99%
“…Shoshin beriberi is the fulminant form of this disease and is characterized by hypotension, tachycardia, and lactic acidosis (1)(2)(3)(4)(5)(6). While thiamine deficiency is also associated with ST-segment elevation in some animal models (7,8), there has been no report of ST-segment elevation in humans with beriberi.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, thiamine deficiency in mice leads to decreased blood catecholamine levels 3. Clinically, human cases of Shoshin beri beri, a form of cardiomyopathy induced by thiamine deficiency, involve increased blood catecholamine levels 4. Therefore, the direct effects of thiamine deficiency on the development of Takotsubo cardiomyopathy cannot be determined based on previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,8) Shoshin beriberi is characterized by hypotension, tachycardia, and lactic acidosis and is mainly encountered in nonalcoholic patients in Asian countries, although it has also been seen in alcoholics in Western countries. 9) No reports about the histopathological features of biopsied endomyocardial specimens from alcoholics and nonalcoholics with Shoshin beriberi have been made although some autopsy studies on the A chest X-ray showed mild cardiomegaly and lung congestion on admission (A). After the treatment, the cardiothoracic ratio was normalized and the lung congestion had disappeared (B).…”
mentioning
confidence: 99%